2014
DOI: 10.1186/1747-597x-9-39
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in subjective discontinuation symptoms associated with ketamine use

Abstract: BackgroundRecent substance abuse research indicates gender differences in the substance-related epidemiology, biological responses, progression to dependence, medical consequences and treatments. Studies exploring human sex-different responses to ketamine are rare and there has been no systemic survey of gender differences in ketamine use. Determining whether females are more susceptible than males to ketamine withdrawal symptoms and adverse effects is important, because it associated with treatment retention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
66
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 38 publications
4
66
1
2
Order By: Relevance
“…In humans, females are more sensitive to ketamine’s withdrawal symptoms (Chen et al 2014), and preclinical research from our lab and others has shown that female rodents respond to lower doses of ketamine than males in measures of antidepressant-like effects (Carrier and Kabbaj 2013; Franceschelli et al 2015; Zanos et al 2016). While ketamine’s abuse potential and reinforcing properties have not been addressed in female rats, a heightened responsiveness to cocaine (Lynch and Carroll 1999, 2000; Swalve et al 2016), opiates (Cicero et al 2003; Lynch and Carroll 1999), nicotine (Swalve et al 2016), cannabinoids (Fattore et al 2007), and phencyclidine (Carroll et al 2005; Carroll et al 2000) have been observed using different self-administration paradigms.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, females are more sensitive to ketamine’s withdrawal symptoms (Chen et al 2014), and preclinical research from our lab and others has shown that female rodents respond to lower doses of ketamine than males in measures of antidepressant-like effects (Carrier and Kabbaj 2013; Franceschelli et al 2015; Zanos et al 2016). While ketamine’s abuse potential and reinforcing properties have not been addressed in female rats, a heightened responsiveness to cocaine (Lynch and Carroll 1999, 2000; Swalve et al 2016), opiates (Cicero et al 2003; Lynch and Carroll 1999), nicotine (Swalve et al 2016), cannabinoids (Fattore et al 2007), and phencyclidine (Carroll et al 2005; Carroll et al 2000) have been observed using different self-administration paradigms.…”
Section: Introductionmentioning
confidence: 99%
“…Women are more vulnerable than men to depression (Kessler, 2003). In a survey of over 1,600 chronic ketamine users females presented significantly more discontinuation symptoms such as anxiety, dysphoria, and tremors and reported more severe cognitive impairment compared with male users (Chen et al, 2014). Preclinical work also suggested sex differences in the behavioral effects of ketamine.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown withdrawal effects from ketamine use. Female ketamine users may show more severe withdrawal-associated cognitive impairment than male users (Fattore et al, 2009;Chen et al, 2014). Furthermore, in humans the abuse potential of oral ketamine (65 and 100 mg) is robust enough to have it being suggested as a positive control for evaluating abuse potential of other psychedelic compounds (Shram et al, 2011).…”
Section: F N-methyl-d-aspartate Receptor Antagonistsmentioning
confidence: 99%